iSCAN-V2: A One-Pot RT-RPA–CRISPR/Cas12b Assay for Point-of-Care SARS-CoV-2 Detection - Aman, Rashid; Marsic, Tin; Sivakrishna Rao, Gundra; Mahas, Ahmed; Ali, Zahir; Alsanea, Madain; Al-Qahtani, Ahmed; Alhamlan, Fatimah; Mahfouz, Magdy (Frontiers in Bioengineering and Biotechnology, 2022)
Rapid, specific, and sensitive detection platforms are prerequisites for early pathogen detection to efficiently contain and control the spread of contagious diseases. Robust and portable point-of-care (POC) methods are indispensable for mass screening of SARS-CoV-2. Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas)-based nucleic acid detection technologies coupled with isothermal amplification methods provide a straightforward and easy-to-handle platform for detecting SARS-CoV-2 at POC, low-resource settings. Recently, we developed iSCAN, a two-pot system based on coupled loop-mediated isothermal amplification (LAMP) and CRISPR/Cas12a reactions. However, in two-pot systems, the tubes must be opened to conduct both reactions; two-pot systems thus have higher inherent risks of cross-contamination and a more cumbersome workflow. In this study, we developed and optimized iSCAN-V2, a one-pot reverse transcription-recombinase polymerase amplification (RT-RPA)-coupled CRISPR/Cas12b-based assay for SARS-CoV-2 detection, at a single temperature in less than an hour. Compared to Cas12a, Cas12b worked more efficiently in the iSCAN-V2 detection platform. We assessed and determined the critical factors, and present detailed guidelines and considerations for developing and establishing a one-pot assay. Clinical validation of our iSCAN-V2 detection module with reverse transcription-quantitative PCR (RT-qPCR) on patient samples showed 93.75% sensitivity and 100% specificity. Furthermore, we coupled our assay with a low-cost, commercially available fluorescence visualizer to enable its in-field deployment and use for SARS-CoV2 detection. Taken together, our optimized iSCAN-V2 detection platform displays critical features of a POC molecular diagnostic device to enable mass-scale screening of SARS-CoV-2 in low-resource settings.